Analisis Buku Ajar Matematika Smp Kelas VII Ditinjau Dari Aspek Materi Dan Penyajian di Kabupaten Sukoharjo - Pratiwi, Heni Nur, Drs. Ariyanto, M.Pd (2016)
The purpose of this study was to determine the quality of math textbook class VII used in Sukoharjo district in terms of aspects of matter and presentation. This research is a qualitative descriptive. Because the school in Sukoharjo many who do not use textbooks, the books that will be analyzed is the book LKS (Student Worksheet). From the observation of some junior high school in Sukoharjo, researchers took a book which is a textbook of mathematics most used in teaching and learning are books bouquet MGMPs LKS (Council Subject Teacher) Junior Mathematical issue Percada Regional Company (PD. Percada). The results of the analysis on the assessment of the first phase of the books analyzed obtain a positive answer 5 of 9 points of assessment. The analysis of the phase II assessment LKS book bouquet MGMPs Junior Mathematical PD Company publications. Percada to obtain components of the feasibility of the contents of an average of 72.69% and for the presentation component of 62.39%. Based on these studies it can be concluded that the book bouquet MGMPs LKS Junior Mathematical publications PD. Percada have the appropriate criteria for eligibility component content and suitable for presentation based on standard components BSNP. Recommended to teachers who use SMP Math worksheets essay published MGMPs PD. Percada notice a few things that are still not in accordance with the criteria of a good book as it has researchers have documented. But in general, this book has reached the appropriate criteria based on standard BSNP. Keywords: textbook, analysis and presentation materials, instruments BSNP